2010
DOI: 10.1080/10888700903579903
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Publicly Sponsored Neutering Programs on Animal Population Dynamics at Animal Shelters: The New Hampshire and Austin Experiences

Abstract: This study found that government-funded surgical sterilization of companion animals has been widely promoted as a means of decreasing shelter intake and euthanasia. However, little information is available about the true impact of these programs on community and shelter nonhuman animal population dynamics. This study estimated the impact of the Animal Population Control Program in New Hampshire by comparing shelter intake and euthanasia data before and after the onset of the neutering initiative. Regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 4 publications
(5 reference statements)
1
40
0
Order By: Relevance
“…The intervention area in Portland was approximately five square miles in size, was determined based on shelter intake, and was compared to control areas of the same size within the same county. Kass [2] and Scarlett [3] were both county level studies, White [4] studied the state of New Hampshire and the work in Austin [4] was based on zip codes that were not selected based on shelter intake. The county and state study area sizes could have made it more difficult to find solid changes and attribute those changes primarily to the spay/neuter clinic (the intervention).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention area in Portland was approximately five square miles in size, was determined based on shelter intake, and was compared to control areas of the same size within the same county. Kass [2] and Scarlett [3] were both county level studies, White [4] studied the state of New Hampshire and the work in Austin [4] was based on zip codes that were not selected based on shelter intake. The county and state study area sizes could have made it more difficult to find solid changes and attribute those changes primarily to the spay/neuter clinic (the intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Their results are varied but suggest that cat intake may be more sensitive to spay/neuter efforts than dogs [2]- [4]. They also illustrate some of the difficulties in studying community level interventions including needing very large numbers of animals receiving spay/neuter to have an impact.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Sterilisation clearly plays a significant role in excess cat management, both nationally and internationally. A recent U.S. study demonstrated a significant decrease in cat admissions and euthanasia at local shelters after a government-funded sterilisation initiative was introduced (White, Jefferson et al 2010). Indeed, mandatory spay or neutering has often been considered by welfare groups, government and councils as a possible legislative requirement, to be introduced with the intention of reducing the cat population and therefore the number of cat admissions to shelters (Marsh 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Marston (2009) Ensuring cats are sterilised before they are able to reproduce will continue to be an important strategy in reducing the number of excess and unwanted kittens admitted to shelters in Australia and the U.S. (Marsh 2010, White, Jefferson et al 2010). Many relinquished animals have visited a veterinarian prior to relinquishment (Salman, New et al 1998).…”
Section: Discussionmentioning
confidence: 99%